Competitive Procurement With Ex Post Moral Hazard - Indranil Chakraborty; Fahad Khalil; Jacques Lawarree (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Unlike standard auctions, we show that competitive procurement may optimally limit competition or use inefficient allocation rules that award the project to a less efficient firm with positive probability. Procurement projects often involve ex post moral hazard after the competitive process is over. A procurement mechanism must combine an incentive scheme with the auction to guard against firms bidding low to win the contract and then cutting back on effort. While competition helps reduce the rent of efficient firms, it exacerbates the problem due to moral hazard. If allocative efficiency is a requirement, limiting the number of participants may be optimal. Alternatively, the same incentives can be optimally provided using inefficient allocation rules.
Keywords: 330; competitive procurement; auctions; moral hazard